Las vidas del poeta. Conversaciones con Francisco Urondo - Sergio Delgado (Cuadernos LIRICO)
This article studies Francisco Urondo’s (1930-1976) poetic work, especially his last books, marked by political militancy, armed struggle and clandestinity. In particular, its “conversational” dimension is explored. His happy and tireless dialogue with writer friends such as Juan L. Ortiz, Noé Jitrik, Rodolfo Walsh and Juan Gelman, but also with the new generations of poets who read, edit, and study him. In short: where does the life of a poet begin and where does it end?